Photoinduced changes in phytochromes studied by means of low temperature UV-Vis spectroscopy - Goncharenko, Maryna (2018)
Phytochromes are a major family of red-light-sensing kinases that control diverse cellular functions in plants, bacteria and fungi. These proteins must relay structural signals from the sensory site over large distances to regulatory output domains. To accomplish this function, they undergo rather large structural changes from one state to another. The general aim of this work was to study these structural changes and possible protonation states of the photosensory core of the bacteriophytochrome from Deinococcus radiodurans in the intermediate states of the photoreaction, which became possible to observe under low temperatures. Moreover, it was interesting to investigate the role Serine272 in stabilization of both states of the photoreaction. Albeit a large amount of spectroscopic studies, the exact mechanism of the photoreaction remains unclear. This question was addressed by recording absorption spectra of studied phytochrome with the help of UV-Vis spectroscopy performed under low temperatures. To understand the role of Serine272 a site-selective mutation in studied bacteriophytochrome was performed. Purified and concentrated phytochromes were analyzed using SDS-PAGE and UV-Vis spectroscopy methods. Furthermore, an approach to measure UV-Vis spectra at low temperatures was developed. The temperature ranges that can be used to trap phytochromes in the intermediate states of the photocycle were identified. Spectroscopy studies revealed that mutated phytochrome could adopt two reversible states when illuminated with far red and near far red light. This finding contradicted the initial hypothesis about potential effect of serine272 on the stability of the photocycle and the photoreversibility of the process. Low temperature UV-Vis measurements confirmed hypothesis that it is possible to trap the protein in different intermediate states of its photocycle, thereby control the whole process by keeping the temperature at the appropriate level.